Safety and Outcomes of Thrombectomy in Ischemic Stroke With vs Without IV Thrombolysis. (24th August 2021) - Ahmed, Niaz; Mazya, Michael; Nunes, Ana Paiva; Moreira, Tiago; Ollikainen, Jyrki P.; Escudero-Martínez, Irene; Bigliardi, Guido; Dorado, Laura; Dávalos, Antoni; Egido, Jose A.; Tassi, Rossana; Strbian, Daniel; et al.
Abstract : Objective: To test the hypothesis that IV thrombolysis (IVT) treatment before endovascular thrombectomy (EVT) is associated with better outcomes in patients with anterior circulation large artery occlusion (LAO) stroke, we examined a large real-world database, the Safe Implementation of Treatment in Stroke–International Stroke Thrombectomy Register (SITS-ISTR). Methods: We identified centers recording ≥10 consecutive patients in the SITS-ISTR, with at least 70% available modified Rankin Scale (mRS) scores at 3 months during 2014 to 2019. We defined LAO as intracranial internal carotid artery, first and second segment of middle cerebral artery, and first segment of anterior cerebral artery. Main outcomes were functional independence (mRS score 0–2) and death at 3 months and symptomatic intracranial hemorrhage (SICH) per modified SITS–Monitoring Study. We performed propensity score–matched (PSM) and multivariable logistic regression analyses. Results: Of 6, 350 patients from 42 centers, 3, 944 (62.1%) received IVT. IVT + EVT–treated patients had less frequent atrial fibrillation, ongoing anticoagulation, previous stroke, heart failure, and prestroke disability. PSM analysis showed that IVT + EVT–treated patients had a higher rate of functional independence than patients treated with EVT alone (46.4% vs 40.3%, p < 0.001) and a lower rate of death at 3 months (20.3% vs 23.3%, p = 0.035). SICH rates (3.5% vs 3.0%, p = 0.42) were similar in both groups. Multivariate adjustment yielded results consistent with PSM. Conclusion: Pretreatment with IVT was associated with favorable outcomes in EVT-treated LAO stroke in the SITS-ISTR. These findings, while indicative of international routine clinical practice, are limited by observational design, unmeasured confounding, and possible residual confounding by indication. Classification of Evidence: This study provides Class II evidence that IVT before EVT increases the probability of functional independence at 3 months compared to EVT alone.